A cost optimisation policy for handoff rerouting. (26th May 2009) - Rizk, Rawya; Atta, Randa; Ghanbari, Mohammad
A two-phase handoff protocol has been proposed to support interswitch handoff in Wireless Asynchronous Transfer Mode (WATM) networks. An important issue is the determination of the best time to perform Phase 2. In this paper, it is shown that none of the existing conventional path optimisation policies is optimal at all network situations; hence, a general Cost Optimisation Policy (COP) applicable to a wide range of network conditions is proposed. It is based on the decision whether to exclude Phase 2 or select among the best path optimisation policies for this phase. The proposed policy avoids unnecessary path optimisations and achieves the lowest total expected cost at variable mobility factors and network conditions. A comparison between the proposed policy and conventional path optimisation policies is performed. The numerical results show a significant improvement of the total expected cost over conventional path optimisation policies at all network situations.